Sustentabilizando(sustaining): estudo das práticas da limpeza veicular, em empresa de transporte coletivo urbano - Durante, Daniela Giareta (2023)
This thesis articulates sustainability, social practices and organizational studies. Sustainability is widely discussed today, as it is essential for the maintenance of human life and permeated with challenges. The discussion hasn’t tradition in organizational studies and presents an emerging association with social practices. The research was conducted in an urban public transport company, specifically in the practices of vehicle cleaning, which are usually intensive in the use of water, chemicals and human physical effort, being a fertile field for the study of sustainability. In addition, cleaning was highlighted during the covid-19 pandemic, a period that coincided with the collection of empirical data. The objective was to understand the sustainability, in the organization of vehicle cleaning practices, in a Ceara company of urban public transport. An ethnographically inspired case study was carried out on bus cleaning practices. The collection of empirical data occurred in two stages, one in 2019 and another in 2021 and 2022, through document analysis, interviews and observations. The immersion processes in the field, survey and interpretation of empirical data followed the theoretical construction of Schatzki (1996, 1997, 2001a, 2001b, 2005, 2011, 2012, 2013, 2015b, 2019a, 2019b), on social practices and changes for sustainable development. In the company studied, vehicle cleaning happens through seven social practices, which form two bundles and a constellation: internal cleaning, leadership of internal cleaning, evaluation of internal cleaning, basic internal cleaning day, external washing, chassis washing and water reuse. The activities, understandings, rules, teleoaffective structure and material arrangements that make up the practices were described. The practices emerged and perpetuated in the business, incorporating changes. They became more sustainable in time and space, as improvements were implemented in doing changes that have generated better conciliation between economic, social and environmental aspects. The improvements were more linked to materialities, which simultaneously emerged in time and space. There were also changes that generated water waste, reduced cleaning quality and soil contamination, considered setbacks. The thesis built is that sustainability happens in the dynamics of practices. The changes implemented in practice, which improve the production pattern or the consumption pattern, make the practice more sustainable. Thus, sustainability is dynamic, an emerging process, arising from complex human actions, interconnected with materialities, which is called sustentabilizing (sustaining).